2009
DOI: 10.1007/s12010-009-8737-2
|View full text |Cite
|
Sign up to set email alerts
|

The Antifungal Activity of Sarcococca saligna Ethanol Extract and its Combination Effect with Fluconazole against Different Resistant Aspergillus Species

Abstract: Microbial resistance is a major drawback in chemotherapy of microbial or fungal infection disease. In this study, the antifungal activity of ethanol extract of a selected plant (Sarcococca saligna) has been investigated against clinical isolates of Aspergillus niger, Aspergillus treus, Aspergillus flavus, and Aspergillus fumigatus. Also, the enhancement of the antifungal activity of fluconazole by this extract was further evaluated against mentioned test strains. Conventional disk diffusion method was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Many plants have been investigated scientifically for antimicrobial activity and a large number of plant products have been shown to inhibit growth of pathogenic bacteria. A large number of these agents appear to have structures and modes of action that are distinct from those of the antibiotic in current use (Mollazadeh et al, 2010). In our study ethanol and methanol extracts of the A. indica were found to show better sensitivity compared with standard antibiotic Erythromycin.…”
Section: Discussionmentioning
confidence: 99%
“…Many plants have been investigated scientifically for antimicrobial activity and a large number of plant products have been shown to inhibit growth of pathogenic bacteria. A large number of these agents appear to have structures and modes of action that are distinct from those of the antibiotic in current use (Mollazadeh et al, 2010). In our study ethanol and methanol extracts of the A. indica were found to show better sensitivity compared with standard antibiotic Erythromycin.…”
Section: Discussionmentioning
confidence: 99%
“…The LD-50 value of salignine showed less toxicity than pysostigmine and neostigmine (Harris et al, 2009). S. saligna extract has been widely used against pain, malaria, rheumatism and skin infections diseases (Mollazadeh et al, 2010). The alkaloid isolated from methanolic extract of S. saligna showed cardio-suppressant, vasodilator, and tracheal relaxant activities (Ghayur and Gilani, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Scientific research into the antimicrobial properties of many plants has revealed that a wide variety of plant products can impede the growth of dangerous bacteria. Many of these drugs looked to have unique structures and modes of action from those of the antibiotics now in use [ 35 ]. The leaves of M. oleifera contain numerous phytochemicals with antimicrobial properties, including tannins, phenolic compounds, and flavonoids [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%